Amino Silane High Positive Charge Layers: A Stable and Durable Alternative Based on Electrostatic Interactions for Titanium Applications, Combining Antimicrobial and Biological Properties - dos S. Silva, João Pedro; Mireski, Mariana; Mallor-Solís, Irene; Borges, Maria Helena Rossy; Piazza, Rodolfo Debone [UNESP]; Marques, Rodrigo Fernando Costa [UNESP]; Cruz, Nilson [UNESP]; Rangel, Elidiane C. [UNESP]; Fortulan, Carlos A.; da Silva, José H. D. [UNESP]; Geringer, Jean; Aparicio, Conrado; et al. (American Chemical Society (ACS), 2025)
Cationic coatings on titanium surfaces are a promising approach for dental and biomedical implants due to their low-cost antimicrobial effect and no need for antibiotics. These coatings are applied on hydroxylated (-OH) surfaces using silanes, such as 3-aminopropyltriethoxysilane (APTES). However, it is unclear whether the concentration of this organofunctional compound affects surface charge or potential toxicity. This study investigated how different concentrations of APTES in cationic coatings on titanium samples influence electrostatic behavior and interactions with bacteria and mesenchymal stem cells (MSCs). Titanium discs served as controls (Ti group) and were first treated by plasma electrolytic oxidation (PEO) to generate -OH groups (PEO group). Subsequently, APTES was applied at 83.8, 167.6, and 251.4 mM, forming PEO+APTES0.3, PEO+APTES0.6, and PEO+APTES0.9 groups, respectively. Surfaces were characterized by scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS), Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), contact angle, Zeta potential, and profilometry. Microbiological assays assessed initial bacterial adhesion (1 h) and biofilm formation (24 h) using Staphylococcus aureus and Escherichia coli. Cell metabolism was assessed on days 1, 3, and 8, while cell viability was assessed on days 1 and 3 using mesenchymal stem cells. PEO-treated surfaces showed porous morphology, and silanization increased roughness and shifted surfaces toward hydrophobicity. Amines and surface charge changes were confirmed by XPS and Zeta potential. Increasing APTES concentration did not proportionally increase cation number. Crystalline hydroxyapatite oxides were identified following the electrochemical process. SEM, EDS, and FTIR confirmed treatment stability after 28 days of immersion, while tribological tests indicated improved performance for PEO-treated groups. Cationic coatings reduced bacterial adhesion by up to 65%, decreased biofilm Log10 values, and increased dead bacteria proportion. Biocompatibility was confirmed by metabolism and cell viability tests, with the group with lower APTES concentration showing the best performance on day 8, with an 80% higher cell metabolism than day 1. On the other hand, higher concentrations of APTES resulted in reduced cell metabolism. These findings indicate, for the first time, that APTES concentration does not affect electrostatic properties but that lower concentrations are required for cytocompatible cationic coatings.